Instructional Worksheet Development Based on Contextual Learning as Assessment for Learning to Support Numeracy Skills in Elementary Schools - Nurul Mukhlisa; Nurul Hidayah Sapri; Wawan Krismanto (International Journal of Educational Practice and Policy, 2026)
This study was motivated by the low level of mathematical proficiency among students in Indonesia. In addition, teaching materials are dominated by textbooks that consist mainly of text and lack meaningful learning activities. As a result, students struggle to solve real-life problems. Therefore, improvements in numeracy skills are needed, including the development of relevant, contextually appropriate student worksheets as assessment for learning. This study aims to develop worksheets based on contextual learning principles as assessment for learning to facilitate the development of numeracy skills among fifth-grade elementary school students. This study uses the ADDIE development model, but only up to the development stage. The research subjects consisted of all fifth-grade students and teachers at three schools in the city of Parepare, South Sulawesi, located in three different parts of the city. Data were collected through observation, interviews, and questionnaires. The data were analyzed descriptively, qualitatively, and quantitatively. This worksheet is based on the principles of contextual learning, with characteristics of constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment. It presents fractions material with examples and problems from students' daily lives, supported by attractive visual designs and clear instructions for use. It is feasible and practical for elementary school mathematics learning. It can support numeracy skills of elementary school students through contextual learning principal and as assessment for learning with real-time feedback. Thus, students are actively engaged in the learning process, and the learning is meaningful to them because it relates to their daily lives.